Ibdāl Al-Yā’ wa ‘Aksih bi Al-Alif Al-Layyinah fī Kurrāsah Al-Tadrīb “HIKMAH” li Al-Ṭullāb Al-Madrasah Al-‘Āliyyah Al-Ulā bi Jember - Wihdatul Hasanah; Faris Maturedy Ahmad; Fathoni Arifandi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2020)
Teaching material is a crucial component in the learning process. Therefore, teaching materials must be in accordance with the criteria set by the experts to be suitable for use by learners. Arabic teaching materials in this case student worksheets still have errors in aspects of their writing. This certainly makes the wrong words difficult to understand and can even change the meaning. This study aims to analyze errors in the use of alif layyinah and yes'. This study uses a qualitative approach with error analysis in the text. The results of this study are there are 35 errors in writing alif layyinah and yes' in the worksheet book.